Conformities of Origin and Prevalence of Mental Disorders among Child Population in Conditions of Modern Donbass - V.I. Аgarkov; Ye.I. Yevtyshenko; A.A. Mustafina; P.V. Kudymov (Zaslavsky O.Yu., 2013)
The primary mental disorders morbidity in child population (0-17 years old) is within 41.8 ± 0.1 cases on 10 000 persons and overruns a total average regional index. The prevalence of the diseases associated with behavior and mental disorders among child population is 330.2 ± 8.0 cases on 10 000 persons and it is lower than an average regional parameter for all population. There is dependence of incidence and prevalence of psychonosemas in child population on the territorial-residential features of activity. The dynamics of incidence of primary psychonosemas in child population is characterized by wave properties and stably remains within 41.6-44.3 cases on 10 000 persons.